Explaining Waiting-time Variations for Elective Surgery Across OECD Countries - Luigi, Sicilani (OECD Publishing, 2005)
Waiting times for publicly-funded elective surgery are a major health policy concern in many OECD countries (like Australia, Canada, Denmark, Finland, Ireland, Italy, the Netherlands, New Zealand, Norway, Spain, Sweden, and the United Kingdom), but are not a concern in others (like Austria, Belgium, France, Germany, Japan, Luxembourg, Switzerland, and the United States). This paper contains a comparative analysis of these two groups of countries. It is found...